Anggaran kehilangan pendapatan akibat kematian pramatang pekerja menggunakan model anuiti meningkat - Noriza Majid,; Saiful Hafizah Jaaman,; Noriszura Ismail,; Noor Suhaina Shamsuddin, (Penerbit ukm, 2008)

(untitled)
Each of us aging from 15 to 64 years old generally spent more than one third of our daily hours at work. Based on the latest study carried out by the International Labor Organization in year 2005, the number of accidents and sickness due to work hazard is more than two million lives per year and this scenario is increasing every year due to the rapid industrial growth especially in a developing country. Based on the statistics published by Jabatan Perangkaan Malaysia in year 2005, the total number of deaths for the Malaysian citizens aging from 20 to 35 years old due to various types of death accidents is 7,249 and this contributes 0.07 percent of the total Malaysian work force in the same year. This percentage is increasing every year. Death accidents have resulted in various implications to the society and to the nation as a whole. One of the main implications is the loss of active and potential work force in industry. The objective of this study is to estimate the potential loss due to premature death which is estimated by discounting to the present the deceased’s expected future earning. For example, the total future income loss of an employee aging 27 years old is nearly RM600,000. Premature deaths also make an impact on the productivity of the country. Due the the total premature deaths in 2004, our country has incurred an estimated loss of RM66 billions whereas in 2005 the incurred estimated loss is RM71 billions